The effects of music therapy on pain and anxiety in young nulliparous patients undergoing laparoscopic cystectomy for endometriosis: a randomized controlled trial - Wenwei Li; Huiyan Feng; Xiaohui Yang; Yue Meng; Yuebo Yang; Qingjian Ye (Journal of Psychosomatic Obstetrics and Gynecology)
Background Endometriosis (EMS) is associated with a markedly increased incidence of depression and anxiety, primarily due to cyclic pain, concerns about infertility from impaired ovarian function, and fear of disease recurrence. Surgery and its associated pain may trigger both emotional and physiological stress responses. Young, nulliparous patients with fertility intentions often experience additional psychological burdens related to surgical safety, postoperative recovery, and the potential impact on future fertility. Music has been shown to promote relaxation, reduce tension and anxiety, and alleviate pain. However, no studies have evaluated the postoperative effects of music therapy in this specific patient population.Objective To investigate whether music therapy can effectively reduce postoperative pain and alleviate perioperative anxiety in young patients with fertility desires undergoing laparoscopic cystectomy for endometriotic ovarian cysts, and to explore its potential as a simple, non-pharmacological intervention.Methods/Design A single-center, two-arm, single-masked randomized controlled trial (RCT).Setting The Third Affiliated Hospital of Sun Yat-sen University (a teaching hospital).Participants A total of 149 patients were included for analysis, with 75 assigned to the music group and 74 to the control group.Intervention Perioperative music therapy administered to young, nulliparous patients with fertility intentions undergoing laparoscopic cystectomy for EMS.Results One participant withdrew during follow-up, and 149 patients were included in the final analysis. Baseline characteristics—including age, BMI, marital status, preoperative VAS scores, and GAD-7 scores and anxiety levels—showed no significant differences between groups. Postoperative VAS scores at 6 h (p = 0.20), Day 1 (p = 0.438), Day 3 (p = 0.714), and Day 7 (p = 0.899) revealed no significant differences. Similarly, GAD-7 scores and anxiety severity levels on postoperative Day 1 (p = 0.541; p = 0.984), Day 3 (p = 0.287; p = 0.436), and Day 7 (p = 0.468; p = 0.703) showed no statistical significance between groups.Conclusion Music therapy may serve as an adjunctive intervention for young, nulliparous patients with fertility intentions undergoing laparoscopic cystectomy for endometriosis; however, no significant effects were observed in reducing perioperative anxiety or postoperative pain in this population.